Content of undergraduate biology core curricula in selected teacher training institutions in Cebu City - Almase, Araceli Gonzales 1933- (s.n.], 1969)
This study analyzed the content of the undergraduate biology core curricula for BSE biology majors in three teaching training institutions in Cebu City with the procedures utilized by the Panel on Undergradaute Major Curricula of the CUEBS in its report on the content of core curricula in biology. Findings revealed some prominent defects common to all the biology core curricula examined.